Performance of proex c and pretect hpv‐proofer e6/e7 mrna tests in comparison with the hybrid capture 2 hpv dna test for triaging ascus and lsil cytology. Issue 9 (22nd January 2013) - Alaghehbandan, Reza; Fontaine, Daniel; Bentley, James; Escott, Nicholas; Ghatage, Prafull; Lear, Adrian; Coutlee, Francois; Ratnam, Samuel
<x xml:space="preserve">Abstract</x> The clinical usefulness of the ProEx C (Becton Dickinson) and PreTect HPV‐Proofer E6/E7 mRNA tests (Proofer; Norchip) for the triage of ASCUS and LSIL cytology was determined in comparison with the Hybrid Capture 2 HPV DNA test (HC2; Qiagen). The study population consisted of women with a history of abnormal cytology referred to colposcopy. Histology‐confirmed CIN 2+ served as the disease endpoint. The study was based on 1, 360 women (mean age 30.7 years), of whom 380 had CIN 2+. Among 315 with ASCUS (CIN 2+, n = 67), the sensitivities of ProEx C, Proofer, and HC2 to detect CIN 2+ were, 71.6, 71.6, and 95.5%, respectively, with a corresponding specificity of 74.6, 74.2, and 35.1%. Among 363 with LSIL (CIN 2+, n = 108), the sensitivities of ProEx C, Proofer, and HC2 were, 67.6, 74.1, and 96.3%, respectively, with a corresponding specificity of 60, 68.2, and 18.4%. Among 225 HC2‐positive ASCUS (CIN 2+, n = 64), 105 tested positive by ProEx C, reducing colposcopy referral by 53.3% and detecting 71.9% of CIN 2+; Proofer was positive in 112/225, reducing colposcopy referral by 50.2% and detecting 75.0% of CIN 2+. Among 312 HC2‐positive LSIL (CIN 2+, n = 104), 160 tested positive by ProEx C, reducing coloposcopy referral by 48.7% and detecting 66.3% of CIN 2+; Proofer was positive in 159/312, reducing colposcopy referral by 49.0% and detecting 75.0% of CIN 2+. In conclusion, both ProEx C and Proofer have a similar performance profile with a significantly higher specificity but lower sensitivity than HC2 for the detection of CIN 2+. Consequently, although they can reduce colposcopy referral, they will miss a proportion of CIN 2+ cases. This is a major limitation and should be taken into account if these tests are considered for ASCUS or LSIL triage. Diagn. Cytopathol. 2013;41:767–775. © 2013 Wiley Periodicals, Inc.